Sistem Pengendalian Internal Persediaan Barang Dagang Pada CV. XYZ - Labitta, Anandini Alyaa; Zainab (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
This research aims to determine the internal control of merchandise inventory at CV. XYZ. The research method used is a qualitative method and the data collection techniques used are library research and field research. The data analysis techniques used are data reduction and data display. The results of this research indicate that the implementation of internal control at CV XYZ has not been implemented properly. This is because there are still several weaknesses in several components of internal control of merchandise inventory, namely the existence of multiple positions in running the organization and not recording inventory expenditure on inventory cards or warehouse cards.